Etnodizajn a ludowość w polskim wzornictwie - Ewa Klekot (Artium Quaestiones, 2021)
In the first decade of the 2000s, a new wave of “folk inspirations” became visible in the work of Polish designers, which was celebrated by exhibitions, publications, conferences and a special festival. Interestingly, all the Polish-language coverage of these events almost unanimously avoided Polish vocabulary suggesting any connection with “folk” (n.: lud, adj.: ludowy) and used the English-sounding term “etnodizajn” (or “ethnodesign”), which actually did not exist in any official Polish or English dictionary. “Etnodizajn” is definitely not the first case when Polish designers have used the “natural resources” of the “folk art tradition”. This article discusses the early 21st century etnodizajn as embedded in the Romantic tradition of understanding the meaning of the folk, pointing at its endurance both in design practices and cultural politics. Following the design strategies of companies and studios linked to etnodizajn, the author presents, on one hand, projects that neatly fit into a century-old strategies of purely formal inspirations, and on the other, those projects that search beyond the beaten track of folk art.